Fungal species isolated from Quercus castaneifolia in Hyrcanian Forests, North of Iran (Biodiversitas Journal of Biological Diversity, 2016)
Kavosi MR, Feridon F, Hajizadeh G. 2013. Fungal species isolated from Quercus castaneifolia in Hyrcanian Forests, North of Iran. Biodiversitas 14: 61-66. In order to isolate and identify of fungi associated with Quercus castaneifolia seed, sampling carried out in Shast-Kalate, Ghorogh, Loveh and Golestan forest. Collected seeds sterilized and then separated sections including: outer section of seed (crust) and inner seed section (endosperm). Each section of seed tissue is cultured on potato dextrose agar media. After sub-culture and providing of the fungi pure cultures, various species isolated and identified by spores characteristics, their size and color, including: Aspergillus flavus, A. niger, Curvularia affinis, Trichoderma harzianum, Trichothecium roseum, Eurotium rubrum, E. amstelodami, Penicillium implicatum, P. fellutanum, Diplodia sp. Nigrospora gossypi, Alternaria alternata , Fusarium oxysporum and Beltrania santapaui. The most frequency of fungus in Shast-Kalate forest was P. implicatum by 74% of frequency within seed section, the most frequency in Ghorogh and Loveh Forest was P. fellutanum with 63 and 66% of frequency within seed section respectively and the most frequency in Golestan forest was B. santapaui by 51% of frequency outer seed section. The result showed diversity of the fungi on the outer seed section is higher than within seed section. The results also showed during several isolation a saprophyte fungus always could be finding on the acorn seeds. This is the comprehensive report on fungi associated with Quercus castaneifolia seed in Hyrcanian forest, North of Iran.